Catch up growth after use of infliximab in children with inflammatory bowel disease (IBD). (4th April 2011) - Kishore, S; Mitton, S
Abstract : Introduction/background: Achieving optimal growth is fundamental in the management of children with inflammatory bowel disease as one in four cases with IBD present in childhood and the majority during their pubertal spurt.15–40% of children with Crohn's disease have either short stature or reduction in growth velocity at presentation. Aim: To determine whether infliximab could achieve catch up growth in children with refractory and severe inflammatory bowel disease. Methodology: We retrospectively reviewed the case notes of the children who received infliximab from 1999 to 2009. Growth measurements (Height for age Z-scores) prior and a year or more after infliximab were extracted and Paired t test was used for statistical analysis. Results: Indications for starting induction course infliximab were severe Crohn's disease (CD) (71%), fistulising CD (22.5%), acute severe colitis (6.5%). All were treated with conventional immunomodulators and 13% had bowel surgery prior to infliximab. Age at diagnosis: median (range) 12.2 years (6.5–16.5 years). Age at start of infliximab: median (range) 14 years (7–19 years). Interval between diagnosis and start of infliximab: median (range) 18 months (10 days–7 years). Duration of infliximab treatment: median (range) 4 years (1–10 years). 31 children had induction course of infliximab. 25/31 responded, 4/5 did not respond (3/4 went to surgery), 1/5 had hypersensitivity reaction and 1/5 got lost to follow-up. Of the four non responders two had second induction, one child responded but could have maintenance infliximab due to PCT funding issues. One child developed anaphylaxis and was commenced on adalimumab. 23/25 who responded commenced maintenance, one child had no maintenance as the colitis resolved and the other child had PCT funding problems. Subsequently funding granted, had second induction and maintenance therapy. 4/5 relapsed after stopping maintenance and 3/23 relapsed while on maintenance. Statistically significant mean difference in growth velocity pre and post infliximab therapy was noted (p=0.0044); 95% CI (0.10 to 0.45 SDS/year). 5/31 (16%) had side-effects (3 minor-headache & dizziness; 1 hypersensitivity; 1 anaphylaxis). Episodic treatment was given in two patients due to PCT funding issues. Conclusion: 25/31 (80%) responded to induction with infliximab. 23/31 (74%) children on maintenance infliximab remained in remission after 1 year and therefore continued maintenance therapy. Children on maintenance infliximab achieved significant catch up growth.